2012
DOI: 10.4236/psych.2012.311144
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Olfactory Perception in Depression: Relationship between Self-Evaluation and Autonomic Response

Abstract: This study aimed to improve the understanding of hedonic perception in depression using the olfactory modality. We evaluated physiological (heart rate measures) and hedonic responses (subjective rating scale) obtained from 30 unipolar depressed inpatients and 30 healthy controls. The stimuli were two odorants with contrasting hedonic valence, vanillin (pleasant) and butyric acid (foul-smelling), presented at three different concentrations and in nine binary mixtures. Compared to controls, the depressed subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Concerning odor hedonic perception, only two studies have shown unchanged scores between depressed patients and healthy controls [ 89 ] before or after antidepressant treatment [ 92 ]. For the majority of the investigations, this parameter is influenced by depressive state [ 46 , 47 , 85 , 86 , 95 , 101 ]. Atanasova et al [ 95 ] showed that depressed patients would perceive unpleasant odors as more unpleasant (negative olfactory alliesthesia), while pleasant odorants would be perceived as less pleasant (olfactory anhedonia) in comparison to controls.…”
Section: What Is the Link Between Olfaction And Depression?mentioning
confidence: 99%
“…Concerning odor hedonic perception, only two studies have shown unchanged scores between depressed patients and healthy controls [ 89 ] before or after antidepressant treatment [ 92 ]. For the majority of the investigations, this parameter is influenced by depressive state [ 46 , 47 , 85 , 86 , 95 , 101 ]. Atanasova et al [ 95 ] showed that depressed patients would perceive unpleasant odors as more unpleasant (negative olfactory alliesthesia), while pleasant odorants would be perceived as less pleasant (olfactory anhedonia) in comparison to controls.…”
Section: What Is the Link Between Olfaction And Depression?mentioning
confidence: 99%
“…Dysfunctions in the prefrontal cortex, as related to depression, are thus hypothesized to have a direct impact on pleasantness ratings. To date, most sensory studies of MDD patients suggest that depressed www.nature.com/scientificreports/ patients perceive "unpleasant" odours to be significantly worse than healthy controls 45 . However, research using "pleasant" odours has produced mixed results, with some observing differences between depressed and healthy individuals 45 , but others detecting no such differences 17 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, most sensory studies of MDD patients suggest that depressed www.nature.com/scientificreports/ patients perceive "unpleasant" odours to be significantly worse than healthy controls 45 . However, research using "pleasant" odours has produced mixed results, with some observing differences between depressed and healthy individuals 45 , but others detecting no such differences 17 . These inconsistent results may be attributable to the use of different testing odorants.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of olfactory studies and mood disorders have focused on the perception of single odorants. To date, only a few studies have investigated olfactory perception in major depression using odor mixtures ( Atanasova et al, 2010 ; Atanasova, 2012 ; Naudin et al, 2012 ). However, studies using odor mixtures are of specific interest because complex olfactory stimuli reflect daily life situations, which is important in the study of anhedonia (failure to gain pleasure from normal pleasant experiences).…”
Section: Implications Of Odor Mixtures Processing In Individuals Withmentioning
confidence: 99%
“…Anhedonia is considered as a core symptom of major depression in an objective way. Using binary mixtures of both pleasant (vanillin) and unpleasant (butyric acid) odorants at three different iso-intense concentrations, it has been shown that depressed patients perceived the majority of odor mixtures (67%) as significantly less pleasant compared to healthy subjects ( Atanasova et al, 2010 ; Atanasova, 2012 ). Depressed subjects also had low performance in correctly identifying the odor of the odorants within the binary iso-intense mixture, and they more readily perceived the unpleasant compound compared to control subjects.…”
Section: Implications Of Odor Mixtures Processing In Individuals Withmentioning
confidence: 99%